THE FOUNDATIONS OF CREDITOR’S LIABILITY IN GRATUITOUS CONTRACTS IN CROATIAN MEDIEVAL LAW - Lachner, Višnja; Kasap, Jelena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Gratuitous bailments are the most common legal affairs in everyday legal transactions. The informality that distinguishes them from other legal affairs, on the one hand, facilitates their application, while on the other hand, complicates the legal position of the contracting parties in the case of breach of contractual obligations. Liability for breach of contractual obligation equally affects both contractors, creditor and debtor. However, since the debtor is a contracting party that in accordance with the principle of utility benefits the most from the conclusion of a gratuitous legal affair, the discussions about obligations and the criteria of liability of creditor have been rare since the occurrence of the earliest legal systems. This is not surprising given that fact that the gratuitous bailment are almost, without exception, is affair concluded between friends and acquaintances marked by the trust of the contracting parties. The foundations of privileged liability of creditors in Western European legal systems, as well as in Croatian law, are based on Roman legal principles, which have been, through the legal norms of the ius commune, reciprocated into the modern legal provisions of law of obligations. Since the issue of creditors’ liability in gratuitous bailments was not included in the Croatian scientific literature, this research will seek to determine the basis of liability of the lender, the depositor and the donor in Croatian law, trough the legal and historical analysis of available sources of Croatian medieval law, and their comparison, but also explain in more detail the reasons for the unique solutions contained in the Croatian Law of obligations.